THE RULES OF HAZFUL OF RASM UTHMAN'S LETTERS: An Analytical Study of the Book of Al-Muqni' Fi Ma'rifati Marsumu Mashahifi Ahlul Amshar Li Abu Amr Uthman Ibn Sa'id Ad-Dani - Herman Herman; Aceng Zakaria; Muslim Muslim; Budi Setiawan (Al - Tadabbur: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
The writing of the Qur'an during the caliphate was a significant phase in Islamic history, where the collection and writing of revelations were carried out to preserve the authenticity of the text. This study aims to analyze the rules of Hazful Huruf Rasm Uthmani in the book Al-Muqni’ by Abu Amr Uthman Ibn Sa'id Ad-Dani, as well as its contribution to the science of Qur'anic rasm. The method used is qualitative research with a literature study approach, which includes an analysis of various works by related scholars. The results of the study indicate that in the book Al-Muqni’ by Abu Daud, the rules of hazf alif, ya, wawu, and lam play a crucial role in maintaining the clarity and beauty of the meanings of the holy verses. Each category of hazf contributes to the preservation of the correct recitation and enriches the language of the Qur'an. Although there are differing opinions among scholars regarding the omission of letters, a deep understanding of these rules is essential to avoid errors in recitation. In conclusion, this study emphasizes the importance of the rules of Hazful Huruf in the writing of the Qur'an and the contribution of the book Al-Muqni’ in preserving the science of rasm, which supports the tradition of correct recitation in Islam.